Assessment of Tertiary Education Readiness of the Pioneering Senior High School Graduates in a Private Higher Education Institution in Northern Mindanao, Philippines - Mortiz, Jo Niza B.; Digamon, Jayson S. (Future Science / FSH-PH Publications, 2023)
Secondary school graduates entering tertiary education must possess the skills and knowledge to adapt rapidly to the ever-changing landscape of a knowledge-based economy. This study assessed the cognitive and non-cognitive college readiness levels of the 127 pioneering senior high school graduates of the Philippine K-12 Program enrolled as first-year college students in a private Higher Education Institution (HEI) in Northern Mindanao, Philippines. Data gathered for this descriptive research were collected using two standardized tests (OLSAT and 16PF). Results revealed that many students had a below-average cognitive level and average non-cognitive skills implying that they were not ready for the tertiary level cognitively but were college-prepared non-cognitively. It was concluded that assessing students' college readiness levels proved imperative to ensure that standards of the chosen programs are met vis-à-vis students' skills. The researchers recommend that Higher Education Institutions strengthen and institutionalize readiness assessment that will serve as a basis for bridging and remediation program for identified cognitively unprepared college students.